2005
DOI: 10.1063/1.1861147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface topology on the formation of oxide islands on Cu surfaces

Abstract: We examined the effects of surface topology on the nucleation and growth of Cu 2 O oxide islands during the initial oxidation stages of Cu͑100͒ and Cu͑110͒ surfaces by in situ ultrahigh vacuum transmission electron microscopy and ex situ atomic force microscopy. Our observations indicate that nucleation of three dimensional oxide islands on single crystal surfaces is homogenous, surface defects and dislocations play a very limited role as preferential sites for oxide nucleation. On the other hand, grain bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…Using TEM observations, they found that the nucleation rate of oxide islands at 350 C on Cu(111) is much faster than that on the Cu(100) and Cu(110) surfaces. 7,70 To understand these results, we return to the original structures of the Cu(100), Cu(110), and Cu(111) surfaces. The Cu(100) surface has the most open structure and rapidly dissociates O 2 at hollow sites, as observed in experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using TEM observations, they found that the nucleation rate of oxide islands at 350 C on Cu(111) is much faster than that on the Cu(100) and Cu(110) surfaces. 7,70 To understand these results, we return to the original structures of the Cu(100), Cu(110), and Cu(111) surfaces. The Cu(100) surface has the most open structure and rapidly dissociates O 2 at hollow sites, as observed in experiments.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous experimental and theoretical studies have shown that the kinetics and morphology of Cu oxidation are complex and influenced by many factors, including surface orientation, ambient temperature, surface defects, and electric fields. [2][3][4][5][6][7][8][9] Most previous studies have focused on the formation of a monolayer (ML) of surface oxides. [10][11][12][13][14][15][16][17][18][19][20][21] However, the process of oxygen transport into the Cu sub-surface is a key step for the transformation between the oxygenated Cu surfaces and bulk oxides.…”
Section: Introductionmentioning
confidence: 99%
“…While some metals and semimetals can grow oxide layers homogeneously without the aid of impurities or surface defects (such as Ru (0001) 254,255 showed that this is not the case on Cu(100) and Cu(110) films. It is indeed possible, considering the different nature of oxide formation on the three low-index surfaces, that different defects play a more or less important role in different oxide nucleation conditions.…”
Section: Nucleation Sitesmentioning
confidence: 99%
“…The oxidation of copper has been studied extensively on single crystals [42][43][44] and alloy systems [45] . Surface oxide films have been found to form in parallel with extensive dissolution and sub-surface oxidation processes.…”
Section: Redox Chemistry Of Cu: Oxidation Of Cu 2 O To Cuomentioning
confidence: 99%